2000
DOI: 10.1046/j.1365-294x.2000.01075.x
|View full text |Cite
|
Sign up to set email alerts
|

Markers derived from amplified fragment length polymorphism gels for plant ecology and evolution studies

Abstract: We describe the types of polymerase chain reaction (PCR) markers that we have isolated using amplified fragment length polymorphisms (AFLP) in closely related taxa from diverse plant genera. With these markers, both inter- and intraspecific differences have been identified. The characterization of the nucleotide sequences and fragment length polymorphisms of such AFLP-derived PCR markers is promising for investigating the ecology and evolution of closely related plant taxa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 11 publications
(13 reference statements)
2
16
0
Order By: Relevance
“…This study and an earlier one which reported on AFLP-derived SCAR markers for other New Zealand plants (McLenachan et al 2000) suggest that standard conventional markers, such as the nuclear ITS region, provide limited resolution for characterising closely related selections of even morphologically diverse genera such as Phormium. Our results show that higher levels of resolution can be found using marker systems such as ISSR and AFLP.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…This study and an earlier one which reported on AFLP-derived SCAR markers for other New Zealand plants (McLenachan et al 2000) suggest that standard conventional markers, such as the nuclear ITS region, provide limited resolution for characterising closely related selections of even morphologically diverse genera such as Phormium. Our results show that higher levels of resolution can be found using marker systems such as ISSR and AFLP.…”
Section: Discussionmentioning
confidence: 62%
“…Amplified fragment length polymorphisms (AFLP) and intersimple sequence repeats (ISSR) have also been applied to distinguish closely related taxa in natural populations of plants (e.g., Esselman et al 1999;Perrie et al 2000). Some concern has been raised over the use of fingerprinting methods for testing phylogenetic relationships (e.g., Swofford et al 1996;Yang et al 1996;McLenachan et al 2000). For example, presence or absence of particular bands may be non-independent, and amplification of fragments may be influenced by quality and quantity of DNA template, rendering results unrepeatable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(b) The SCAR-based approach where screening for variability in RAPD-generated DNA fragments among closely related species precedes design of primers (modified from Bailey et al 2004). regions (SCARs; Melotto et al 1996) that can be screened as potentially useful sequence loci prior to development of specific primers (Shaw et al 2003;Bailey et al 2004). This strategy is a modified version of the AFLP-based method of McLenachan et al (2000) for characterizing population level gel-based markers. Under this method, PCR products of equal length amplified across a subset of species using commercially available random primers are excised, cloned, sequenced and aligned to evaluate variability (figure 4b; Bailey et al 2004).…”
Section: Strategies For Selecting Nuclear Sequence Locimentioning
confidence: 99%
“…Also, the reproducibility of AFLP markers is lower than for single locus markers and homoplasy of equal-sized fragments cannot be excluded. Finally, the application of AFLP markers for wood identification faces difficulties because of the need for goodquality genomic DNA (McLenachan et al 2000), whereas quality and quantity of DNA from wood is generally low (De Filippis and Magel 1998;Dumolin-Lapègue et al 1999;Deguilloux et al 2002;Rachmayanti et al 2006Rachmayanti et al , 2009. Thus, AFLP markers need to be converted into locus-specific markers [sequence characterized amplified region (SCAR markers)].…”
Section: Introductionmentioning
confidence: 99%